2001
DOI: 10.1046/j.1439-0442.2001.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Observation of Subclinical Chronic Copper Poisoning in Two Sheep Breeds

Abstract: Fourteen castrated male sheep of two breeds, the Mutton Merino (MMB) and Blackhead Suffolk cross breed (BSC), were exposed to an oral copper (Cu) intake of 3.7 mg/day per kg body weight for 84 days (high Cu group, HCu), and 11 castrated male sheep received a daily oral Cu intake of 0.16 mg/day per kg body weight (controls). Liver Cu concentration was measured in liver biopsies until 2.7 years after Cu overdose. Haematologic parameters, plasma Cu, enzymes and metabolites were analysed and post-mortem examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 14 publications
6
45
2
2
Order By: Relevance
“…9,11,13 Serum Cu and other traditional biochemical variables have limited diagnostic value in terms of Cu accumulation, 9,13 and the best results were observed in sheep in association with alterations of hepatic enzymes. 7 Some researchers 13 have concluded that the most reliable factor in diagnosing early accumulation of Cu is determination of the serum activities of aspartate aminotransferase (AST) and gamma-glutamyl transferase (GGT), not the determination of serum Cu concentration, acid phosphatase, and sorbitol dehydrogenase serum activities. Consequently, it is necessary to determine the usefulness of measuring hepatic enzyme activities in cases of Cu accumulation, in which animals are close to an intoxication episode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,11,13 Serum Cu and other traditional biochemical variables have limited diagnostic value in terms of Cu accumulation, 9,13 and the best results were observed in sheep in association with alterations of hepatic enzymes. 7 Some researchers 13 have concluded that the most reliable factor in diagnosing early accumulation of Cu is determination of the serum activities of aspartate aminotransferase (AST) and gamma-glutamyl transferase (GGT), not the determination of serum Cu concentration, acid phosphatase, and sorbitol dehydrogenase serum activities. Consequently, it is necessary to determine the usefulness of measuring hepatic enzyme activities in cases of Cu accumulation, in which animals are close to an intoxication episode.…”
mentioning
confidence: 99%
“…9 Additionally, glutamate dehydrogenase has elevated plasma activity even after the period of Cu overload and presents better results as an indicator of hepatic Cu accumulation than do AST and GGT in sheep. 7 However, because of their availability in Brazil and as a result of importation restrictions, these enzymatic evaluations were not performed as part of the current study. To evaluate these results, further studies are necessary with a larger number of animals using different enzymatic combinations in cattle and buffalo with high Cu intake that leads to a hemolytic crisis over a short period.…”
mentioning
confidence: 99%
“…On the dead animals liver function cannot be tested and cupraemia changes to values within normal range within few hours (Bohman et al 1984, Underwood & Suttle 1999 as happened in the calves evaluated (Table 2). In these fatal cases of ACP, liver Cu concentration has no value, because there is no longer Cu accumulation period in the liver as occurs in CCP (Humann-Ziehank et al 2001, Mendel et al 2007, when the high transference rate of Cu is the lethal factor (Giuliodori et al 1997). The liver Cu values found conϐirm this statement (Table 3).…”
Section: Discussionmentioning
confidence: 93%
“…During this outbreak the animals received the mineral supplement for almost one year before the first case was observed and all sheep died acutely after the onset of clinical signs. On the other hand, sheep experimentally intoxicated did not demonstrate clinical signs consistent with CCP more than 2.5 yr after the first administration of daily doses of Cu (HUMANN-ZIEHANK et al, 2001). The hepatic accumulation of Cu may take weeks or more than a year to occur without any corresponding clinical manifestation, after which a sudden release of Cu into the circulatory system initiates clinical signs typical of CCP (ISHMAEL; GOPINATH; HOWELL, 1971;KIMBERLING, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The intoxication results in severe economic losses due to death of affected sheep and the implantation of control measures (KIMBERLING, 1988;RADOSTITS et al, 2002). All ovine breeds are considered highly susceptible to Cu poisoning, but some breeds (North Ronaldsay, Charollais, Texel, and Suffolk) are more predisposed than others (ANGUS, 2000); however other authors have considered the Mutton Merino and Suffolk cross-breeds resistant to copper intoxication (HUMANN-ZIEHANK et al, 2001). There is no apparent sex or age predisposition of sheep to Cu poisoning (ANGUS, 2000), but mature British ewes may develop the disease more frequently than other categories of animals (KIMBERLING, 1988).…”
Section: Introductionmentioning
confidence: 99%